LEGAL ENTITIES AS THE MAIN PARTICIPANTS IN BUSINESS ACTIVITY IN RUSSIA AND CHINA - O. Berzin; E. Shliagina (BRICS Law Journal, 2019)
The legal entity is one of the most common forms of business activity in the Russian Federation and the People’s Republic of China. The regulation of legal entities in Russia and China has changed in recent years, which makes the study of this issue especially relevant. This article explores and compares the concept of business activity, the system of legal entities and several types of particular legal entities in regard to companies found in Russia and China. The research concludes that the system of legal entities in the Russian Federation has an exhaustive regulation that facilitates the interpretation of the civil legislation and allows distinguishing the relevant characteristics of any type of organization. In China, there was no unified system of legal entities until 2017. While the General Provisions of the Civil Law of the People’s Republic of China adopted in 2017 is a serious and important attempt to establish a system of legal entities, the law does not contain the essential characteristics of legal entities; additionally, a number of the provisions of the legal acts in force devoted to the regulation of the activities of legal entities have not yet been brought in line with the new law.